Review of Understanding formulaic language: A second language acquisition perspective; Editors: Anna Siyanova-Chanturia, Ana Pellicer-Sánchez; Publisher: Routledge, 2019; ISBN: 9781138634978; Pages: 278 - Alhudithi, Ella (Studies in Second Language Learning and Teaching, 2021)
The discussion of mechanisms enhancing the acquisition of formulaic language (FL) has been flourishing in recent decades, progressing from describing the concept to revealing its use in various registers: spoken, written, and hybrid. With each domain of linguistics approaching FL in a distinct way, the book Understanding Formulaic Language: A Second Language Acquisition Perspective by Anna Siyanova-Chanturia and Ana Pellicer-Sánchez presents a more inclusive view of recent research contributions emerging from different fields, in addition to pointing to critical gaps that need to be addressed in future research. The appeal of the book is that it covers a broad range of topics related to FL, from theoretical perspectives to practical applications. This breadth of coverage is the first effort to foster mutual understanding among linguists and to emphasize its connection with second language acquisition (SLA).